If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = -1(-2x + 8) + -13 Reorder the terms: 19 = -1(8 + -2x) + -13 19 = (8 * -1 + -2x * -1) + -13 19 = (-8 + 2x) + -13 Reorder the terms: 19 = -8 + -13 + 2x Combine like terms: -8 + -13 = -21 19 = -21 + 2x Solving 19 = -21 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 19 + -2x = -21 + 2x + -2x Combine like terms: 2x + -2x = 0 19 + -2x = -21 + 0 19 + -2x = -21 Add '-19' to each side of the equation. 19 + -19 + -2x = -21 + -19 Combine like terms: 19 + -19 = 0 0 + -2x = -21 + -19 -2x = -21 + -19 Combine like terms: -21 + -19 = -40 -2x = -40 Divide each side by '-2'. x = 20 Simplifying x = 20
| -26-x=-5x+30 | | 48l+140=260 | | (-2+10)-(-6x+5y+12)+(x+8y-16)= | | 3x+(-10)=-1 | | 5y+y=-60 | | 7n=3n+3 | | 50+.25x=43+.35x | | 7x-x+3=2x+x | | -4(6x-3)=24 | | 10+90(x+2)-7+3(2x-8)=-1 | | 4x-(-8)=24 | | f(2x)=x^2-10x+1 | | 8-4v=-(v-6)-5(v+1) | | x+2x+2=3x-15 | | 4(-7x+4)=-264 | | 20z-8= | | 2x-1=2x+9 | | -10x+2=32 | | 3(3p+7)=15(p-4) | | 73.5=4.37+y | | 2y-7=3y-23 | | 7.5+2.18x=60 | | 7x-4y+3a= | | 50-Z=10 | | -10x+2=22 | | f(x+y)=x^2-10x+1 | | 5x+8=-3x-12 | | 25+13f=-14 | | -4(-6x-3)=24 | | 13-7n=-71 | | 6x-(-5)=29 | | 6x-4x=3(2x+1) |